Adapted Portuguese folk dance intervention for subacute rehabilitation post-stroke: study protocol - Fernandes, Júlio Belo; Domingos, Josefa; Família, Carlos; Veríssimo, Júlio; Castanheira, Patrícia; Menezes, Carla; Vicente, Célia; Santos, Claúdia; Marvão, Elisabete; Coelho, Joana; Mestre, Joana; Teodoro, Joana; et al. (Frontiers in Public Health, 2023)
Dance can be an innovative, well-accepted, and effective therapy for stroke survivors. The present protocol aims to assess the feasibility of adapted Portuguese folk dance as a post stroke rehabilitative activity. We will use a mixed-methods pilot study convenience sampling to recruit 16 stroke survivors with mild–moderate lower limb paresis from a rehabilitation center in Lisbon and Tagus Valley. In addition to usual care, participants will attend 3 days per week 1-h dance exercise for 8 weeks. The dance style used for this intervention will be an adaptation of the Portuguese folk dance. Assessment will be conducted before and immediately after the program intervention. Acceptability will be assessed by four key domains (enrollment, retention, satisfaction, and recommendation to others). Safety will be assessed based on the number and type of adverse events. Feasibility will be assessed based on balance performance and functional mobility. Quantitative data will be analyzed through descriptive statistics for sample characterization, followed by inferential statistics to evaluate differences in the balance recovery and functional mobility scores between the initial and final assessment. Qualitative data will be analyzed using an inductive process of content analysis. The Portuguese folk dance program has the potential to improve balance outcomes and functional mobility. Our results will help validate Portuguese folk dance as a tool for rehabilitation settings for stroke survivors. The potential of our program to enhance balance outcomes and functional mobility among stroke survivors bears implications for aging and public health initiatives. Positive results from this study could pave the way for integrating dance-based rehabilitative activities into standard stroke rehabilitation protocols, catering to older stroke survivors’ specific needs and preferences.